Synthesis of peri-Diarylated Naphthalimides via Double Decarboxylative Cross-Coupling Reaction - Kantarod, Kritchasorn; Naweephattana, Phiphob; Reutrakul, Vichai; Pohmakotr, Manat; Soorukram, Darunee; Kuhakarn, Chutima; Surawatanawong, Panida; Leowanawat, Pawaret (Synthesis, 2019)
A facile method for the synthesis of peri-diarylated naphthalimides was developed by using a palladium-catalyzed double decarboxylative cross-coupling reaction. The present work offers a convenient approach for tuning the optical properties of naphthalimide derivatives.
Keywords: peri functionalization; naphthalimides; decarboxylative cross-coupling; palladium; catalysis